2013
DOI: 10.5194/nhess-13-2109-2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatially limited mud turbidites on the Cascadia margin: segmented earthquake ruptures?

Abstract: Abstract. A series of 23 thin, mostly mud-silt turbidites are found interspersed between larger, well-dated and regionally correlated paleoseismic sandy turbidites that extend along most of the Cascadia margin, northwestern United States. Investigation of the structure, distribution, and sedimentology of these thin mud-silt units supports the interpretation of these units as turbidites originating on the continental slope. Interpretation of mud turbidites is inhibited by bioturbation and lower response to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 111 publications
(211 reference statements)
0
44
0
1
Order By: Relevance
“…Estimates of peak coseismic slip for the 2011 Tohoku-oki earthquake exceed 60 m near the Japan Trench (e.g., Ozawa et al, 2011;Wei et al, 2012;Yamazaki et al, 2011). If subduction zones store energy over long intervals that span several earthquake cycles, higher slip defi cits than inferred in this study might be achieved (i.e., supercycles; Sieh et al, 2008;Goldfi nger et al, 2013a).…”
Section: Evidence Supporting a Range Of Cascadia Earthquake Scenariosmentioning
confidence: 64%
See 1 more Smart Citation
“…Estimates of peak coseismic slip for the 2011 Tohoku-oki earthquake exceed 60 m near the Japan Trench (e.g., Ozawa et al, 2011;Wei et al, 2012;Yamazaki et al, 2011). If subduction zones store energy over long intervals that span several earthquake cycles, higher slip defi cits than inferred in this study might be achieved (i.e., supercycles; Sieh et al, 2008;Goldfi nger et al, 2013a).…”
Section: Evidence Supporting a Range Of Cascadia Earthquake Scenariosmentioning
confidence: 64%
“…1A). The along-strike continuity of the mud turbidites is supported by 29 new cores and high-resolution compressed high-intensity radar pulse (CHIRP) seismic-refl ection profi les that image stratigraphy between core sites (Goldfi nger et al, 2013b). Goldfi nger et al (2012) showed that each of the 41 turbidites in the 10,000 yr Cascadia record meets a variety of criteria that favor synchronous triggering by plate-boundary earthquakes.…”
Section: Evidence Of Earthquake-triggered Turbidity Currents Offshorementioning
confidence: 97%
“…Individual turbidites can only be mapped with high‐resolution seismic sources in specific cases (e.g. Goldfinger et al ., ) and/or when they are megaturbidtes (for example, this study; Schnellmann et al ., ). However, determining the source region of the turbidites that are not linked to MTDs from this type of data is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, medical computed tomography (CT) scanners have become common in the nondestructive analysis of sediment cores [St-Onge et al, 2007], including high-resolution reconstructions of relative or calibrated density for paleoenvironmental interpretation [Boespflug et al, 1995;Ashi, 1997;Lis e-Pronovost et al, 2009;St-Onge and Long, 2009;Støren et al, 2010;Davies et al, 2011;Dorfman et al, 2015], assessment of coring deformation [Ashi, 1997;Barletta et al, 2010;Walczak et al, 2017], and variations in sedimentological structures or components [Michaud et al, 2003;Gagnoud et al, 2009;Goldfinger et al, 2013;Mena et al, 2015;Patton et al, 2015]. Medical CT scanners measure the attenuation of X-rays, a function of density and atomic number, and store these values in pixels as relative gray scale values or Hounsfield units (HU), achieving resolution around 0.5 3 0.5 3 0.5 mm [Hounsfield, 1973].…”
Section: Introductionmentioning
confidence: 99%